Understanding Riverine Urbanism in Kalimantan through Diachronic Approach: Case Study of Lanting Settlements in Sintang, Indonesia - Mira Sophia Lubis; Dalhar Susanto; Triatno Yudo Harjoko (Journal of Architectural Design and Urbanism, 2021)
Famous for its large rivers, Kalimantan is one of the islands in Indonesia that is characterized by a river-cultured society, where lanting or floating dwelling is one of various types of river settlements that represents a unique but also complex relationship between man and river. Despite their existence being in line with the historical development of river cities in Kalimantan, today’s urban lantings have come to be stigmatized as slums, due to society’s biased perspectives, and the dominance of the planning paradigm that is oriented towards “modern” land-based urban planning. Using the qualitative historical analysis method in the case study of lanting dwellings in Sintang, West Kalimantan, this study interprets the analytical dimensions of the complex relations between space, power and resources, which changes over time. Exploring the political-economic and ecological history shows the long journey of lanting’s existence that gave understanding of today’s lanting conditions, as well as understanding about the development of the cities themselves. This study concludes that the concept of river cities or waterfront cities in Kalimantan should be understood in a broader sense, beyond merely aesthetic and environmental considerations. Riverine settlement has deep historical roots in many Kalimantan cities and also represents complex relationships between city-hinterland and river-related urbanization process under the political-economic and ecological changes. Thus, consideration of the diachronic aspects of city-river relations should be an important basis for planning future Kalimantan cities.